2005
DOI: 10.1007/s00542-005-0057-z
|View full text |Cite
|
Sign up to set email alerts
|

Vibration of hard disk drive spindle systems with distributed journal bearing forces

Abstract: This paper is to analyze vibration of fluid dynamic bearing spindles with distributed journal bearing forces. The dynamical model is developed to predict the transverse vibration of the disk-spindle systems in HDD where an aspect ratio of the bearing width to the shaft length is significant and the shaft is likely flexible. In such spindles the journal bearing functions as a continuous support, providing the distributed restoring and damping forces, and is therefore modeled as distributed linear spring and dam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Few researchers have experimentally investigated the dynamic characteristics of HDD systems with the herringbone-microgrooved journal bearing. Jintanawan [10] presented a dynamic model of a disk-spindle system with distributed forces in herringbonemicrogrooved journal bearing for predicting the transverse vibrations of HDD spindles. Miwa et al [11] proposed a new method for evaluating the damping and frequency characteristics of fluid dynamic bearing (FDB) spindle, using a high-frequency vibration base.…”
Section: Introductionmentioning
confidence: 99%
“…Few researchers have experimentally investigated the dynamic characteristics of HDD systems with the herringbone-microgrooved journal bearing. Jintanawan [10] presented a dynamic model of a disk-spindle system with distributed forces in herringbonemicrogrooved journal bearing for predicting the transverse vibrations of HDD spindles. Miwa et al [11] proposed a new method for evaluating the damping and frequency characteristics of fluid dynamic bearing (FDB) spindle, using a high-frequency vibration base.…”
Section: Introductionmentioning
confidence: 99%
“…The improvement of vibration control has been discussed from various aspects and solutions proposed such as by applying several control algorithms, developing new design of actuator, embedding secondary actuator to the system and others [2] It has been shown by Jintanawan that the vibration increases with higher HDD rotational speed [6]. Wood suggested that the HDD must be stiff enough to suppress the vibration [7].…”
Section: Introductionmentioning
confidence: 99%